Conversable worlds literature, contention, and community 1762 to 1830 - Mee, Jon. (Oxford : Oxford University Press, 2011)
Around 1700 a new commercial society was emerging that thought of its values as the product of exchanges between citizens. A welter of publications-periodical essays, novels, and poetry-enjoined the virtues of conversation and were discussed in book clubs and literary societies, creating their own conversable worlds.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Conversation in literature; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 18th century; Literature and society -- Great Britain -- History -- 19th century